Blunt Isolated Small Bowel Perforation Intervention: Does a Delay in Management Matter?. (4th June 2020) - Hong, Sung Yong; Kim, Se Hun; Kim, Ki Hoon
Abstract : Purpose . Blunt small bowel injury is rare, and its timely diagnosis may be difficult. The effects of a delayed intervention on prognosis are unclear. We aimed to determine whether the time to surgical intervention affects outcomes in patients with blunt small bowel perforation. Methods . The study was performed between March 2010 and December 2018 in adults (age >18 years) who initially underwent computed tomography and small bowel surgery only and survived more than one day postoperatively. They were categorized into three groups based on injury-to-surgery time intervals: ≤8, 8–24, and >24 h; similarly, they were also categorized into two groups of ≤24 and >24 h. Results . Bowel resection, length of stay (LOS), intensive care unit (ICU) LOS, morbidity, and mortality were analyzed as outcomes in 52 patients. The number of patients in the three groups (≤8, 8–24, and >24 h) based on the time-to-surgery was 33, 13, and 6, respectively. On comparing the three groups, there were no significant differences in LOS (24 [18–35], 21 [10–40], and 28 [20–98] days, respectively; p = 0.321 ), ICU LOS (2 [1–12], 4 [2–26], and 11 [7–14] days; respectively, p = 0.153 ), mortality (3% ( n  = 1), 15% ( n  = 2), and 0%, respectively; p = 0.291 ), and morbidity (46% ( n  = 15), 39% ( n  = 5), and 50% ( n  = 3), respectively; p = 0.871 ). However, there was a significant difference between the groups in bowel resection (67% ( n  = 22), 31% ( n  = 4), and 83% ( n  = 5), respectively; p = 0.037 ). Additionally, there was no significant difference in outcomes between the two groups (≤24 and >24 h) with small bowel perforation. Conclusions . Delay in surgical intervention following blunt abdominal trauma may not affect the outcomes of patients with small bowel injuries, such as LOS, ICU LOS, morbidity, and mortality, except bowel resection.